Challenges Towards Sustainable Tourism for Regional Development of Vlore Region - Prifti, Aleks; Zenelaj, Engjellushe (European Journal of Sustainable Development, 2013)
Vlora has great potential for regional development. Tourism can be as a catalyst for theeconomic growth but still have many challenges for sustainable tourism regionaldevelopment. Regional development is one ofthe most important dimensions and key ofEU policy, which is designedto: ensure convergence between the different member statesand regions; ensure regional competitiveness and employment;ensure territorialcooperation. Vlora has all the potential to bean attractive tourismdestination. Resourcesthat it can use to create its distinctive image for tourists are numerous. Across geography,which has spread Vlora region, there are monuments, archaeological item and rare naturalmonuments, natural sites and attractions centuries. Way to understand these apparentlyalready clarified is joining with the tourism environment. Return tourism potential in realestate assets for the rapid development andprosperity of the region, is one of theobjectives with which to measure the role of state institutions, businesses, investitures andpolicies that support, promote, stimulate and develop the sector oh tourism. Tourismdevelopment is facing many challenges related to development and the control urbanity,decentralization process, thegeographical distribution of tourism, exploitation of allresources and tourist potential, the protection of natural and cultural heritage.